MESUJI CASE: IS THERE A VIOLATION OF ECONOMIC RIGHTS? THE AVAILABILITY OF JUDICIAL SETTLEMENT MECHANISM ON THE VIOLATION OF ECONOMIC AND SOCIAL RIGHTS IN INDONESIA - Kusumawati, Erna Dyah; Kusumo, Ayub Torry Satriyo; Sasmini, Sasmini (UI Scholars Hub, 2013)
This article focuses on the factors triggering the Mesuji conflict and the similar cases happening in Indonesia. In addition, this paper seeks to find the available settlement alternatives which can be used to solve the conflict. The study will take a long, hard look on state practices (South Africa and India) concerning on the settlement of the economic and social (socio-economic) rights. The conclusion drawn is that a conflict involving society’s rights and interests should be solved in a comprehensive way. It cannot be solved only by litigation or non-litigation procedures. The Government should establish a policy concerning the regulation on the land expropriation. Also the government should monitor the implementation of the regulation in order to prevent from the abuses carried out by third parties (companies). Thus, the government will protect the socio-economic rights of the society